Endoscopic ultrasound using ultrasound probes for the diagnosis of early esophageal and gastric cancers - Yoshinaga, Shigetaka (Baishideng Publishing Group Co., Limited, 2012)
Endoscopic ultrasound (EUS) devices were first designed and manufactured more than 30 years ago, and since then investigators have reported EUS is effective for determining both the staging and the depth of invasion of esophageal and gastric cancers. We review the present status, the methods, and the findings of EUS when used to diagnose and stage early esophageal and gastric cancer. EUS using high-frequency ultrasound probes is more accurate than conventional EUS for the evaluation of the depth of invasion of superficial esophageal carcinoma. The rates of accurate evaluation of the depth of invasion by EUS using high-frequency ultrasound probes were 70%-88% for intramucosal cancer, and 83%-94% for submucosal invasive cancer. But the sensitivity of EUS using high-frequency ultrasound probes for the diagnosis of submucosal invasive cancer was relatively low, making it difficult to confirm minute submucosal invasion. The accuracy of EUS using high-frequency ultrasound probes for early gastric tumor classification can be up to 80% compared with 63% for conventional EUS, although the accuracy of EUS using high-frequency ultrasound probes relatively decreases for those patients with depressed-type lesions, undifferentiated cancer, concomitant ulceration, expanded indications, type 0-I lesions, and lesions located in the upper-third of the stomach. A 92% overall accuracy rate was achieved when both the endoscopic appearance and the findings from EUS using high-frequency ultrasound probes were considered together for tumor classification. Although EUS using high-frequency ultrasound probes has limitations, it has a high depth of invasion accuracy and is a useful procedure to distinguish lesions in the esophagus and stomach that are indicated for endoscopic resection.